Optimization of far-infrared vacuum drying conditions for Miang leaves (Camellia sinensis var. assamica) using response surface methodology - Sathira Hirun (2018)
© 2015, The Korean Society of Food Science and Technology and Springer Science+Business Media Dordrecht. Far-infrared (FIR) vacuum is an advanced drying technique that has recently been applied in food processing. Optimal drying conditions for processing tea from Miang leaves using FIR vacuum drying were investigated. Response surface methodology with a central composite design was used to design, analyze, and predict the optimal time and temperature conditions for FIR vacuum drying, taking into account the physicochemical properties of Miang leaves. When the temperature increased from 50 to 65°C and the time from 60 to 120 min, the amount of epicatechin, epicatechin gallate, epigallocatechin gallate, and total catechins significantly (p < 0.05) increased while the moisture content and water activity significantly (p < 0.05) decreased, compared with controls. The physicochemical properties of dried Miang leaves were significantly (p > 0.05) influenced by time and temperature, compared with controls. Drying conditions of 65°C for 120 min are recommended for optimization of drying.